Art in the city reduces the feeling of anxiety, stress, and negative mood: A field study examining the impact of artistic intervention in urban public space on well-being - Jan Mikuni; Margot Dehove; Linda Dörrzapf; Martin Karl Moser; Bernd Resch; Pia Böhm; Katharina Prager; Nikita Podolin; Elisabeth Oberzaucher; Helmut Leder (Wellbeing, Space and Society)
Promoting urban well-being is a significant societal task in the context of rapid urbanization. Past research has highlighted that interaction with urban green spaces, such as parks and forests, is key in promoting urban well-being. However, there is limited knowledge regarding the potential in promoting well-being from non-nature elements. In the present study, we explored whether interacting with art could enhance well-being in urban street contexts. In our field experiment, we built two interventions on urban streets, decorating them with either laminated art prints or green elements. We measured subjective and physiological well-being before and after the interaction with the interventions. With this paradigm, we assessed if, not only green, but also artistic interventions can improve well-being. Our results showed that, after interacting with the artistic intervention in an urban environment, the participants reported reduced feelings of anxiety, stress, and negative mood as they did with the green intervention. Further, our results indicate that improvements in well-being were linked to participants’ evaluations of the testing location (restorativeness), of aesthetic quality of the intervention (e.g., beauty, meaningfulness), and of their overall experience (e.g., enjoyment). These findings have significant implications in promoting urban well-being and city planning, as they highlight the potential of art as a novel tool for enhancing urban well-being.